Dietary probiotic ingestion is associated with elevated enterolignans concentration in the United States population, evidenced by NHANES 1999–2010 - Dong, Jialong; Huang, Liufang; Wang, Chuchu; Luo, Xinyi; Wei, Jin; Abuduxukuer, KaiweiSa; Luo, Jianfeng; Zhou, Yifan; Peng, Qing (Frontiers in Nutrition, 2025)
PurposeTo investigate the associations between urinary enterolignans concentration and oral probiotic ingestion using nationally representative data from the United States population.MethodsWe analyzed dietary recall data and urinary enterolignans concentrations from 12,358 eligible participants in the National Health and Nutrition Examination Survey (NHANES) 1999–2010. Linear regression models with comprehensive covariate adjustments were employed to assess associations, accounting for demographic, socioeconomic, health status, and lifestyle factors.ResultsParticipants with dietary probiotic ingestion had higher urinary concentrations of enterolignans, and probiotic ingestion showed robust and profound positive correlations with enterolignans after fully adjusted with multiple confounders (all p values<0.05). Frequent probiotic consumption exerts a more profound and positive impact on enterolignans concentrations than Infrequent probiotic consumption, according to correlation coefficient values in both univariate and multivariate analyses.ConclusionDietary probiotic consumption was significantly associated with elevated urinary enterolignans concentrations in the U.S. population, with high-frequency intake demonstrating a stronger dose–response relationship compared to low-frequency consumption.